Patient–Provider Discussions About Urinary Incontinence Among Older Women - Lane, Giulia I (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Urinary incontinence (UI) is prevalent in women and has been associated with decreased quality of life and institutionalization. Despite this, and the fact that several treatment options exist, few women discuss UI with clinicians. The aim of this study was to examine the proportion of middle aged and older women with urinary incontinence who have discussed UI with clinicians, focusing on female health professionals as a way to examine this question outside of issues of health care access. METHODS: Data are from the Nurses Health Studies (NHS), two ongoing observational, prospective, cohort studies. The surveys collected detailed information about UI, including frequency, amount and type. Women were also asked if they had discussed UI with a clinician. We used multivariable-adjusted logistic regression to estimate odds ratios (OR) of participants reporting discussion about UI. RESULTS: 94,692 women with UI aged 49–91 years old were included in this study. Of these, 34% reported that they had discussed their incontinence with a clinician. Women with daily UI had 4.4 times greater odds of discussing it with clinicians when compared to those with monthly UI (OR = 4.36, 95% confidence interval [CI] 4.06–4.69). When controlling for severity of symptoms, the oldest women, greater than eighty years, were 20% less likely to have discussed UI with their clinician, compared to the youngest women (OR = 0.81, 95% CI 0.73–0.89). CONCLUSIONS: A minority of women with UI, even among health professionals, discuss their symptoms with clinicians. Oldest women were the least likely to discuss their UI with a provider.